2016
DOI: 10.1038/srep36023
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a new model to study effects of periodontal pathogens on cardiovascular diseases

Abstract: Porphyromonas gingivalis (Pg) is a keystone pathogen in the aetiology of chronic periodontitis. However, recent evidence suggests that the bacterium is also able to enter the bloodstream, interact with host cells and tissues, and ultimately contribute to the pathogenesis of cardiovascular disease (CVD). Here we established a novel zebrafish larvae systemic infection model showing that Pg rapidly adheres to and penetrates the zebrafish vascular endothelium causing a dose- and time-dependent mortality with assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Zebrafish maintenance and experimental work was performed in accordance with UK Home Office regulations and the UK Animals (Scientific Procedures) Act 1986. London wild-type zebrafish larvae were maintained as previously described [34]. For infection, methylcellulose-embedded, tricaine-anesthetized dechorionated larvae were injected systemically by direct inoculation into the common cardinal vein at 2 days postfertilization with 500 colony-forming units of C albicans in PBS or PBS alone as control (n = 20 zebrafish injected per treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish maintenance and experimental work was performed in accordance with UK Home Office regulations and the UK Animals (Scientific Procedures) Act 1986. London wild-type zebrafish larvae were maintained as previously described [34]. For infection, methylcellulose-embedded, tricaine-anesthetized dechorionated larvae were injected systemically by direct inoculation into the common cardinal vein at 2 days postfertilization with 500 colony-forming units of C albicans in PBS or PBS alone as control (n = 20 zebrafish injected per treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…Dysregulated adhesion molecule expression may initiate vascular pathology due to abnormally elevated vascular permeability leading to oedema, chronic inflammatory and vascular damage [26]. We recently showed that Pg can cause vascular damage in an in vivo zebrafish larvae model of systemic infection in a gingipain-dependent manner [27], suggesting that these bacterial proteases may be important factors in the development of CVD. Here, we hypothesised that gingipain-dependent cleavage of endothelial cell junction adhesion molecules is important in mediating the vascular damage.…”
Section: Introductionmentioning
confidence: 99%
“…Our aims in this study were to further assess such roles of Csps in L. monocytogenes virulence in vitro using a human macrophage cell line as well as in vivo using a zebrafish embryo based infection model. Zebrafish embryos are an attractive multicellular model for infection studies, that are easily accessible for microscopy due to their translucent nature, and have been widely used in microbial research with various bacteria including L. monocytogenes (Prajsnar et al, 2008 ; Levraud et al, 2009 ; Widziolek et al, 2016 ). Observations from these virulence studies also led us to examine the role of Csps in cellular aggregation as well as in extracellular motility and flagella production of L. monocytogenes .…”
Section: Introductionmentioning
confidence: 99%